Control of linear generator based on hysteresis‐SVPWM current rectification and bidirectional buck/boost converter used for energy storage. Issue 14 (4th August 2021) - Ali, Murad; Haitao, Yu; Yao, Wang; Yilin, Yang
Abstract: The free‐piston Stirling linear generation system has tremendous applications in space power supply, biomass generation, solar thermal generation, factory waste heat generation, and other industrial fields. However, the free‐piston Stirling linear generation system suffered from the disadvantages of fluctuation of output electric energy and self‐starting. To solve the aforesaid problems, a two‐level electric energy conversion control mode which combines three‐phase AC/DC and bidirectional buck/boost DC to DC converter is proposed in this paper to make the generation system with stable output DC power. Then, both the linear and non‐linear mathematical model of the free‐piston Stirling engine are established. Additionally, to improve the performance of frequency and displacement tracking, the traditional proportional‐integral (PI) in the position loop is replaced by Proportional Resonance (PR) controller. Moreover, the Hysteresis‐SVPWM current control strategy with high robustness and dynamic response is applied to the rectifier to realize the unit power factor control of the AC side of the generator and the stability and controllability of the DC side voltage. Finally, the three‐phase voltage Source Rectifier (VSR) and Bi‐directional DC/DC with an appropriate inductance and capacitance for energy storage are modelled. The effectiveness of the proposed system is validated using theoretical analysis and simulations in Matlab.